2022
DOI: 10.1093/ageing/afab245
|View full text |Cite
|
Sign up to set email alerts
|

New horizons in the perioperative care of older adults

Abstract: Older adults undergoing surgery have high perioperative morbidity and mortality. Age-related physiological changes and prevalence of geriatric syndromes such as frailty increase the risk of adverse postoperative outcomes. Geriatricians utilise comprehensive geriatric assessment (CGA) and management to identify and manage geriatric syndromes, and deliver patient-centred perioperative care. Perioperative models of CGA are established for older patients undergoing hip fracture surgery. Recent trials support the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
0
22
1
Order By: Relevance
“…In current literature, studies in the orthogeriatric population predominate, but there seems to be an evolution towards scientific research in other surgical specialties [ 15 ]. However, a recent review showed that only few studies have compared proactive geriatric care with usual care in surgical specialties other than orthopaedic/trauma surgery [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In current literature, studies in the orthogeriatric population predominate, but there seems to be an evolution towards scientific research in other surgical specialties [ 15 ]. However, a recent review showed that only few studies have compared proactive geriatric care with usual care in surgical specialties other than orthopaedic/trauma surgery [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In current literature, studies in the orthogeriatric population predominate, but there seems to be an evolution towards scientific research in other surgical specialties [15]. However, a recent review showed that only few studies have compared proactive geriatric care with usual care in surgical specialties other than orthopaedic/trauma surgery [28]. Important to mention is that geriatric care is well implemented in Belgian hospitals due to a Royal Decree which states that hospitals must provide in acute geriatric hospital wards, an IGCT, a multidisciplinary geriatric day hospital, an outpatient clinic for geriatric patients and a partnership with primary care [10].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the assessment might have been limited to a frailty score only, and indirectly reduced mortality by activating frailty-adapted pathways of care. 21,22 Despite implementation of geriatric medicine services in many surgical centres, work still needs to be done to…”
Section: Discussionmentioning
confidence: 99%
“…By sharing patient centred goals and the perspective of experts in care of the elderly, we can mitigate the perioperative risk and streamline patient flow without compromising our way of work, personal preferences, schedules or control. [18][19][20] Although clear to us that we and our patients only benefit by shared care with our geriatricians, patient reported outcomes will strengthen the case for a shared care model aside from costeffectiveness in a specialty where quality of life may have greater importance than quantity. The practical implementation of our model could provide a framework for other units who may wish to work together in this way.…”
mentioning
confidence: 98%
“…As our population ages and co‐morbid conditions such as diabetes and obesity increase, procedural risk in our patient cohorts will only get higher. By sharing patient centred goals and the perspective of experts in care of the elderly, we can mitigate the perioperative risk and streamline patient flow without compromising our way of work, personal preferences, schedules or control 18–20 . Although clear to us that we and our patients only benefit by shared care with our geriatricians, patient reported outcomes will strengthen the case for a shared care model aside from cost‐effectiveness in a specialty where quality of life may have greater importance than quantity.…”
mentioning
confidence: 99%